Structural, morphological and mechanical properties of hyperbranched polymers coated carbon fibers reinforced DCBA/BA-a composites. Issue 10 (2nd October 2020) - Daham, Abbas; Zegaoui, Abdeldjalil; Ghouti, Hamid Abdelhafid; Derradji, Mehdi; Cai, Wan-an; Wang, Jun; Liu, Wen-bin; Wang, Jun-yi; Moussa, Zaoui
ABSTRACT: In this work, short carbon fibers were first surface-grafted with various amounts of epoxy terminated hyperbranched polymers, and then utilized as reinforcing phases in various thermosetting polymeric blends composed of dicyanate ester of bisphenol-A (DCBA) and bisphenol-A based benzoxazine (BA-a) resins. The Fourier Transform Infrared Spectroscopy (FTIR) test validated the surface modification of the short fibers and confirmed the reaction between the coated fibers and the DCBA/BA-a resin blend. The composites' mechanical properties were evaluated and the obtained results revealed that at the maximum fiber loadings, the bending strength and modulus as well as the impact strength were identified to be 217.8 MPa, 7.1 GPa, and 18.4 kJ/m 2, respectively. The scanning electron microscope (SEM) analysis established that the enhancements were basically attributed to the good dispersion and adhesion of the coated carbon fibers within the resin matrix. Graphical Abstract: uf0001